Shear bond strength comparison of moisture-insensitive primer and self-etching primer - Goswami, Arunima (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: The detrimental effect of moisture on orthodontic bonding has long been known. Hydrophilic bonding materials have been introduced suggesting the possibility of obtaining successful orthodontic bonding to a moisture contaminated enamel surface. AIMS: This study has been performed with an aim to compare the in vitro shear bond strength (SBS) and debonding characteristic of moisture-insensitive primer (MIP) (Transbond MIP) (3M Unitek, South Peck Road, Monrovia, California, USA) and self-etching primer (SEP) (Transbond Plus SEP) (3M Unitek, South Peck Road, Monrovia, California, USA) in combination with a color changing adhesive system (Transbond Plus Color Change) (3M Unitek, South Peck Road, Monrovia, California, USA) under both dry and contaminated condition. SETTINGS AND DESIGN: Randomized controlled clinical study. SUBJECTS AND METHODS: One hundred and twenty freshly extracted teeth for the purpose of orthodontic treatment were collected. Teeth were randomly assigned into four groups, each consisting of 30 specimen and stainless steel brackets were bonded using each primer-adhesive combination under different enamel conditions, that is, dry and enamel contaminated with natural saliva. SBS and adhesive remnant index were calculated for each group. RESULTS: Analysis of variance of SBS for both MIP and SEP under dry and contaminated condition showed no statistical significance (P = 0.5). Chi-square test showed significant difference in debonding characteristics among the test groups (P < 0.001). All the groups showed typical debonding characteristics of separation either at the bracket-adhesive interface or within the adhesive itself. CONCLUSIONS: Moisture contamination did not affect the SBS and adhesive remaining on tooth for both MIP and SEP.